Changes in the State Regulation of the Insurance Services Market of Ukraine: Security Aspect. (Economics and region, 2021)
The purpose of the article is to analyze the changes in the state regulation of the financial services market of Ukraine in the context of increasing the level of financial and economic security of market participants. The methods and parameters of regulating the activities of financial services market entities were generalized. The latest changes in the domestic legislation concerning the supervision and regulation of the financial services market, in particular, the insurance market, in terms of the impact on the level of their economic security were analyzed. It is determined that for effective and safe activity of insurance market participants it is necessary to take into account the level of development of each of the segments in terms of ability to meet increased requirements for: size and capital structure, liquidity, ownership structure, availability of qualified management staff. Attention is paid to the criteria of transparency of the ownership structure of insurance companies. The article contains an analysis of trends in the development of insurance market entities and the impact on them of the supervisory functions transfer to the National Bank of Ukraine. The directions of strengthening the economic security of the financial market insurance segment were determined.
Keywords: financial services market; insurance services market; financial institutions; economic security; financial security; state regulation